Induction of heat-labile enterotoxin synthesis in enterotoxigenic Escherichia coli mitomycin C. - Isaacson, R E (1975)
Introduction of heat-labile toxin (LT) synthesis in enterotocigenic strains of Escherichia coli by mitomycin C (MTC) was demonstrated. Six enteropathogenic strains which produce LT were inducible, exhibiting an 896-fold increase in LT when compared to ininduced cultures. On the other hand, four nonenteropathogens and three other pathogens which produce only the heat-stable toxin were not induced to produce LT. Gel filtration chromatography, antibody neutration, and heat lability studies suggest that the toxin synthesized in the presence of MTC is the same as the toxin synthesized in the absence of MTC.